The Effect of Using One Stay Two Stray Method of Cooperative Learning on Reading Comprehension of Junior High School Students - Nadifah Sekarwangi, Nisrina; Fitrotul Mufaridah; Widya Oktarini (JELP Journal of English Language and Pedagogy, 2025)
This study investigates the impact of the One Stay Two Stray (OSTS) collaborative learning strategy on reading comprehension among junior high school students in Indonesia. Recognizing the challenges faced by students with limited English proficiency, the research employs an experimental design involving two classes from SMPN 1 Tamanan. The experimental group received reading appreciation skills training through the OSTS method, while the control group engaged in traditional individual learning. Data were collected through pre-tests and post-tests, with results analyzed using a t-test to determine statistical significance. Findings indicate that the experimental group demonstrated a significant improvement in reading comprehension, with a post-test mean score of 97.81 compared to 92.85 for the control group. The t-test results (t-value = 2.16) exceeded the critical value (2.01), confirming the effectiveness of the OSTS method in enhancing students' reading skills. This study underscores the importance of collaborative learning strategies in fostering better comprehension abilities in language education